PENGARUH PELATIHAN INSECT BITE RESCUE TERHADAP PENANGANAN KORBAN CEDERA PADA SENGATAN TAWON DI DESA KENONGOSARI SOKO TUBAN - Karyo, Karyo; Ferianto, Kusno; Sayoga, Budi (Jurnal Penelitian Sekolah Tinggi Ilmu Kesehatan Nahdlatul Ulama Tuban, 2021)
Early handling on sting emergencies due to wasp stings are must be handled quickly & appropriatly things that need to be considered  to avoid fatal condition. The treatment of bee sting emergencies  is not yet known by many people and they only do modest treatment by applying cold compresses and leaving the wasp sting marks. The purpose of the study was to determine the effect of insect bite rescue training on the treatment of injured victims of wasp stings in the village Kenongosari Soko Tuban. This study uses a design Pre-Experimental, by one-group design pre-post test design. Simple random sampling used take a sample from 32 respondes. The instrument used are SOP and observation sheets. Data analysis using statistical testsWilcoxon. The results showed then was in scores of 29 respondents who experienced an increase. Analysis of research data using the Wilcoxon test. Wilcoxon test results obtained Asymp results. Sig. (2-tailed) = 0,000 with a significant value <0.05, then H1 is accepted. So it can be concluded that the Insect Bite Rescue Training has an influence on the Behavior of Injuring Victims. And it is hoped that Insect Bite Rescue Training can be applied by for handling when exposed to wasp stings.